Characterizing the sublethal effects of SmartStax PRO dietary exposure on life history traits of the western corn rootworm, Diabrotica virgifera virgifera LeConte - Jordan D. Reinders; Emily E. Reinders; Emily A. Robinson; William J. Moar; Paula A. Price; Graham P. Head; Lance J. Meinke (PLoS ONE, 2022)
The western corn rootworm (WCR), Diabrotica virgifera virgifera LeConte, is an economically important pest of field corn (Zea mays L.) across the United States (U.S.) Corn Belt. Repeated use of transgenic hybrids expressing Bacillus thuringiensis (Bt) proteins has selected for field-evolved resistance to all current rootworm-active Bt proteins. The newest product available for WCR management is SmartStax® PRO, a rootworm-active pyramid containing Cry3Bb1, Cry34/35Ab1 [now reclassified as Gpp34Ab1/Tpp35Ab1] and a new mode of action, DvSnf7 dsRNA. Understanding the fitness of adult WCR after dietary exposure to SmartStax® PRO will identify potential impacts on WCR population dynamics and inform efforts to optimize resistance management strategies. Therefore, the objective of the present study was to characterize the effect of SmartStax® PRO dietary exposure on WCR life history traits. Adult WCR were collected during 2018 and 2019 from emergence tents placed over replicated field plots of SmartStax® PRO or non-rootworm Bt corn at a site with a history of rootworm-Bt trait use and suspected resistance to Cry3Bb1 and Cry34/35Ab1. Adult survival was reduced by 97.1–99.7% in SmartStax® PRO plots relative to the non-rootworm Bt corn plots during the study. Individual male/female pairs were fed different diets of ear tissue to simulate lifetime or adult exposure. Life history parameters measured included adult longevity, adult head capsule width, lifetime female egg production, and egg viability. Results indicate that lifetime or adult exposure to SmartStax® PRO significantly reduced adult longevity and lifetime egg production. Larval exposure to SmartStax® PRO significantly reduced WCR adult size. Results from this study collectively suggest that SmartStax® PRO may negatively impact WCR life history traits, which may lead to reduced population growth when deployed in an area with WCR resistance to Bt traits.